Three Principles of Competency-Based Learning: Mission, Mission, Mission - Rivenbark, William C.; Jacobson, Willow S. (Journal of public affairs education : J-PAE., 2014)
NASPAA adopted new accreditation standards in October 2009, requiring Masters programs of public administration, public policy, and public affairs to adopt and implement competency-based learning. This learning approach, however, is not new to public administration. Scholars have been promoting competency-based education for more than 25 years (Greenhill, Metz, & Stander, 1982). This article expands on the previous work of competency-based education, presenting lessons learned from the experience of the Master of Public Administration (MPA) program at the University of North Carolina at Chapel Hill (UNC). A systematic competency-based learning system was adopted and implemented in support of its mission statement of preparing public service leaders. The purpose of these lessons is to help NASPPA-accredited programs, of all sizes, conceptualize and advance their approaches to competency-based learning, including the need for a shared understanding of the program's mission and the need for faculty flexibility when making curriculum changes.